UJI BEBERAPA KONSENTRASI TEPUNG DAUN SIRIH HUTAN (Piper aduncum L.) UNTUK MENGENDALIKAN HAMA Sitophilus zeamais M. PADA BIJI JAGUNG DI PENYIMPANAN - Harahap .; Khoirummy Rakhmadiah (Jurnal Agroekoteknologi, 2016)
Corn seed in the storage can be experience quality and quantity in July 1st 2017 decrease. In fact, it was caused by Sitophilus zeamais M. pest. The level of S. zeamais M. damage at corn seed could be over than 30%. This research was aimed to find the best concentration betel leaf powder to control S. zeamais M. on corn seed in the storage. Research was conducted at the Laboratory of Plant Pests Faculty of Agriculture University of Riau from October until December 2015. The research used a Randomized Completely Design (RCD) consisting of 5 treatments and 4 replications. The treatments tested were giving some concentration of betel leaf powder around 0, 2, 4, 6, and 8 g / 100 g of corn. Data were analyzed by analysis of variance. The result of that variance was tested further by Duncan's New Multiple Range Test. The result showed that S. zeamais M. which was given the betel leaf powder with different concentration showed the initial time of death, lethal time 50, daily mortality, total mortality, depreciation and accretion individual seed weight S. zeamais M. was different. The betel leaf powder with a concentration of 8 g/100 g of corn could control the S. zeamais M. pest.Keywords: Corn seed, Piper aduncum L., Sitophilus zeamais M.